PROPUESTAS DE DESARROLLO SOSTENIBLE PARA IMPULSAR EL TURISMO EN EL BALNEARIO PUERTO BAJAÑA EN EL CANTON BUENA FE. - Esquivel Parraga, Karla Lisbeth (2024)
The case study Sustainable Development Proposals to Boost Tourism in Puerto Bajaña, Buena Fe city, the objective of this case study is to balance environmental conservation, social well-being, and economic growth. Based on a diagnosis of the balneario, challenges such as the lack of adequate infrastructure and the need to promote responsible tourism practices were identified. Proposed actions include the conservation of natural resources, waste management, community participation, cultural promotion, and the development of sustainable infrastructure. Additionally, management and monitoring strategies are included to ensure the effective implementation of the proposals. The expected results include reducing environmental impact, increasing tourist influx, generating local employment, and improving the community’s quality of life. In conclusion, this study provides a framework for transforming Puerto Bajaña into a sustainable and competitive tourist destination.